Territorial Autonomy in European Democracies: The Case of the Faroe Islands - Stanković, Marko (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
The paper analyses the political and territorial autonomy of the Faroe Islands within the Kingdom of Denmark. After the introductory part, there is a presentation of the basic features of the theoretical concept of territorial autonomy. It is followed by a brief overview of the evolution of the status of the Faroe Islands, which were a Norwegian and Danish colony for centuries, and since the middle of the last century they have acquired autonomous status within the Kingdom of Denmark. The central part of the paper is an analysis of the legal norms that regulate Faroese autonomy, in particular the Home Rule Act of the Faroe Islands of 1948 and two acts from 2005 – the Foreign Policy Act of the Faroe Islands and the Assumption Act of the Faroe Islands. After that, there is an analysis of the current political situation in the Faroe Islands, which is compared with the current situation in Greenland, another autonomous territory within the Kingdom of Denmark. The concluding remarks summarize the research results and offer answers to open legal and political questions.
Keywords: Faroe Islands; Denmark; Kingdom of Denmark; territorial autonomy